1987
DOI: 10.1055/s-2006-962658
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Caffeoylglycosides on Arachidonate Metabolism in Leukocytes

Abstract: The effects of caffeoylglycosides (forsythiaside, suspensaside, acteoside, and 3-hydroxyacteoside), isolated from dried fruits of Forsythia species, on the formations of the 5-lipoxygenase products 5-hydroxy-6,8,11,14-eicosatetraenoic acid (5-HETE) and leukotriene B4 (LTB4), the 15-lipoxygenase product 15-hydroxy-5,8,11,13-eicosastetraenoic acid (15-HETE) and the cyclooxygenase products 12-hydroxy-5,8,10-heptadecatrienoic acid (HHT), thromboxane B2 and 6-keto-PGF1a in rat peritoneal cells and human peripheral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(105 citation statements)
references
References 9 publications
3
100
0
2
Order By: Relevance
“…TxA2 mobilizes Ca2+ from intracellular stores; this intracellular elevation of Ca2+ is likely the final mediator of platelet aggregation and ADP release. It was also demonstrated that even at low concentrations (10 -6 -10 -3 mol/l) resveratrol inhibited the formation of lipoxygenase product and TXB2 by rat peritoneal polymorphonuclear leukocytes, and suppressed ADP-induced platelet aggregation (51).…”
Section: Mechanisms Involved In the Antiaggregatory Effect Of Wine Phmentioning
confidence: 94%
“…TxA2 mobilizes Ca2+ from intracellular stores; this intracellular elevation of Ca2+ is likely the final mediator of platelet aggregation and ADP release. It was also demonstrated that even at low concentrations (10 -6 -10 -3 mol/l) resveratrol inhibited the formation of lipoxygenase product and TXB2 by rat peritoneal polymorphonuclear leukocytes, and suppressed ADP-induced platelet aggregation (51).…”
Section: Mechanisms Involved In the Antiaggregatory Effect Of Wine Phmentioning
confidence: 94%
“…There were several pioneering reports on resveratrol, including a study of resveratrol as an inhibitor of arachidonate metabolism via interactions with 5-lipoxygenase and cyclooxygenase (COX) pathways in leukocytes. 6) However, resveratrol attracted little interest until 1992, when it was postulated to explain some of the cardioprotective effects of red wine. 7) Since that time, many studies have shown that resveratrol can prevent or slow the progression of a variety of conditions, including cancers, cardiovascular diseases, and ischemic injuries, [8][9][10][11][12] as well as enhance stress resistance and extend lifespan.…”
Section: Introductionmentioning
confidence: 99%
“…The polyphenolic phytoalexin resveratrol (3,5,4'-trihydroxytrans-stilbene) became well known as a substance present in grapes and wine, especially in red wine, with pronounced pharmacological effects such as inhibition of cyclooxygenase I, antioxidant and anti-inflammatory activity, 1 inhibition of platelet aggregation and coagulation, 2 modulation of arachidonic acid metabolism, 3 lipid metabolism 4 and inhibition of low density lipoprotein oxidation. 5 ± 7 Based on these properties, it was suggested that resveratrol is a protective agent against cardiovascular diseases and may be responsible for the socalled French paradox, 8,9 namely, the lower frequency of myocardial disease in the population of Southern France, in spite of an intake of fat and cholesterol in amounts constituting a risk factor for cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%